Carcass composition in three different breeds of chicken and their correlation with growth performance - Idris, Lokman Hakim; Abu Bakar @ Zakaria, Md Zuki; Goh, Yong Meng; Sazili, Awis Qurni; Mohamed Mustapha, Noordin (Universiti Putra Malaysia Press, 2011)
This study was undertaken with the aim to determine the carcass composition of three breeds of chicken and their correlation with growth performance. For this purpose, fifty Red Jungle Fowl (Gallus gallus Spadiceus), fifty Malaysian indigenous chickens (Gallus gallus Domesticus) and fifty broiler chickens (ROSS) were used in this study. The chickens in each group were sacrificed at 1, 10, 20, 56, and 120 days post-hatching. The results showed that there were significant differences in the parameters measured between the high performance breed (commercial broilers), and the lower performance breeds (Red Jungle Fowl and Malaysian Indigenous chickens), although they were reared under the same environment and received the same feed, management and other facilities. Meanwhile, relative whole carcass weight, bone and fat weights in the commercial broiler were the highest compared to indigenous chickens and red jungle fowl at (p<0.05).